Peningkatan Indeks Pertanaman Padi pada Musim Tanam ke Dua di Kecamatan Ngawen, Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta - Arif Anshori; Damasus Riyanto; Suradal Suradal (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Increasing rice production through area expansion is very difficult to do in Gunungkidul Regency. Increasing the rice cropping index is an alternative option in increasing rice production, supported by supplementary irrigation. This study aimed to determine the increase in the rice cropping index from 1 to 2 by utilizing supplementary irrigation from the Oyo River Dam. The research was conducted at Sambirejo, Watusigar Village, Ngawen Sub-district, Gunungkidul Regency, Special Region of Yogyakarta during the second planting season in 2019. During planting time, rainfall was observed to determine irrigation time. In conditions without rain, the irrigation interval was not more than 5 days. The randomized completely block design (RCBD) was used to determine the suitability variety of Inpari 19, Inpari 24, Inpari 30, Inpari 42 and Sidenuk in the conditions of the second planting season, complete with a package of rice production technology components. The data collected includes rainfall, harvest age and rice productivity. Farmers' perceptions was explored to determine acceptance of technology components. The results showed that supplementary irrigation from the Oyo River Dam was sufficient to increase the rice planting index in the second planting season. Variety of Inpari 24, Inpari 19 and Inpari 30 had high productivity, with Inpari 19 being prospectively developed for rice cultivation in the second planting season. Most farmers receive a package of technology components, but were constrained by capital for irrigation.